Annual report - AmInvestment Group Berhad; AmBank group (Kuala Lumpur : AmInvestment Group Berhad, 2006)
An annual report of AmInvestment Group Berhad, AmBank Group for the year 2006
PTSL : 2006
System requirements : Windows pentium III or later, 64MB RAM, windows 95/98/ME/2000/XP, sound card and speakers, 4X speed CD-ROM drive or faster, high color (16 bit) at a resolution of 800 X 600 pixels ; power macintosh or later, 64 MB RAM, MAC OS 8.5 or later, 4X speed CD-ROM drive or faster, high color (16 bit) at a resolution of 800 X 600 pixels
Keywords: Banks and banking -- Malaysia -- Periodicals; Banks and banking -- Periodicals